Juridical Analysis of The Inclusion of Criminal Sanctions in Government Regulations in Lieu of Law - Timomor, Adensi; Lolong, Wenly R. J.; Pangalila, Theodorus (Technium Social Sciences Journal, 2023)
The Law on Formation of Legislation states that only laws and regional regulations can contain criminal sanctions, but in Indonesian constitutional practice, there is a Government Regulation in Lieu of Law (Perppu) which contains criminal sanctions, namely Perppu Number 2 of 2017 concerning Community Organizations. Of course, this is contrary to the Law on the Formation of Legislation. The purpose of this research is to analyze whether Perppu can contain criminal sanctions as well as laws. While the method used in this research is normative legal research. The results of the study show that based on the Law on Formation of Legislation, the Perppu has the same position as the Law, while the difference lies in its formulation. Laws are made by the President together with the DPR while Perppu are only made by the President. Regarding the material content of criminal sanctions in the Perppu it should not be allowed because the Perppu is a regulation made unilaterally by the President. Also remembering that the loading of criminal material in a law is very important to get the approval of the people’s representatives because this is directly related to individual dignity and rights human rights as citizens.